Adhesions are the major cause of complications in operative gynecology. (August 2016) - Herrmann, Anja; De Wilde, Rudy Leon
Abstract : Adhesion formation has been found to be highly prevalent in patients with a history of operations or inflammatory peritoneal processes. These patients are at a high risk of serious intraoperative complications during a subsequent operation if adhesiolysis is performed. These complications include bowel perforation, ureteral or bladder injury, and vascular injury. In order to minimize the risk of these complications, adhesiolysis should only be performed by experienced surgeons, and intraoperative strategies must be adopted. The reduction of the overall incidence of adhesions is essential for subsequent surgical treatments. Anti-adhesion strategies must be adopted for preventing the reoccurrence of adhesions after abdominopelvic operations. The strategies employed to reduce the risk and the overall incidence of adhesions have been elucidated in this article. Highlights: Adhesiolysis is associated with serious complications. Visualization of potentially endangered anatomical structures during adhesiolysis is necessary. Adhesiolysis is a demanding procedure. Adhesiolysis should only be performed by experienced surgeons. Surgeons should adopt anti-adhesion strategies.